The due diligence handbook : corporate governance, risk management and business planning - Spedding, Linda S., 1952- (CIMA, 2009)
This book brings together practical information on legislation, primary sources, codes and best practice guidance in one volume. A practical handbook for business directors who wish to minimise financial, legal and reputational risks. It combines all matters concerning corporate governance with due diligence issues and in doing so provides you with the information and tools you need to help you protect your business when under taking due diligence, particularly when making international acquisitions. The book provides clear guidance and case studies to help all involved understand the complexity of issues and to demonstrate the detailed work that is necessary both to ensure that the benefits of an acquisition can be realised and that there are no unexpected problems, for example through damage to corporate reputation that more that offsets the targeted benefits. As high profile business failures tarnish the reputation of international business it is essential that business responds by having the policies and practices in place in day-to-day operations and in particular, as this book demonstrates, when a major business development such as an acquisition is being implemented. Following the initial era of codes in the UK and regulation in the USA and major debates as regards the best approach to corporate governance in the common law countries, controversy has developed over which approach is really more appropriate for business planning purposes and risk management. Given the trend for many UK companies listed on the US market to de-list in favour of the more British approach to corporate governance and in light of more European corporate scandals this book provides a comparative analysis of the European frameworks for governance. The EU approach and the individual jurisdictions of Germany, Italy, the Netherlands and France, in terms of their practical success or failure (with case studies)is covered. With the debate over an EU Constitution and the political stance of Germany (under the Merkel leadership) during its Presidency to revive the Constitution the book assesses the EU approach generally at a time when the competitiveness of companies and key business sectors must consider the thrusting economies of India and China in particular. The link with competitiveness is an increasingly crucial matter. In connection with due diligence, the book provides an update of the business world in light of the world?s economy and links corporate governance, risk management and business planning to reflect such business, political and regulatory trends and changes. In recent years there has been much comment and feedback on the effectiveness of the Sarbanes-Oxley approach to corporate governance and many updates on business ethics and sustainability issues, which this book also covers in the context of due diligence. In addition, since there has been a major shift in business awareness to develop, or be seen to develop, a more enlightened approach to climate change coverage of this area is include in the book in the appropriate context of governance, risk management and business planning, as well as the trends in different parts of the world (USA (and some others v many others!). There are case studies within the book on how business is operating in order to respond to this issue with an international dimension and comparison. The whole debate over being carbon neutral has impacted on the airline industry in particular and has relevance to how industry sectors should balance the interests of the different stakeholders and cope with rather fast attitude changes of the media and public (and the regulators). The importance of energy security has raised key competitiveness issues of major interest and commercial significance. Moreover the angle of fraud in this sector has become more evident. The area of energy security within this book is tied into ethical accounting, fraud, risk etc. and economic crime. These new areas can be set against the background issue of how much of this comes into play with due diligence. How far is this now part of risk management in todays business world. New legislation is covered in terms of developments with the UK Companies Act and Directors? duties with an increasing need to understand reputational concerns and off balance sheet values since the withdrawal of OFR. The only book that looks at due diligence how it's used and how to get it right in the context of Corporate Governance, Reputational Risk Management and Business Planning. A practical guide with case studies and checklists illustrating key business drivers which enable you to monitor risk management effectively. Covers the latest regulatory UK and EU framework for due diligence, and doing business across international boundaries, India, China, USA etc.